A Mammoth in the Park: Palaeontology, Press and Popular Culture in Barcelona (1870–1910). (August 2016) - Valls Plana, Laura
Abstract: This paper focuses on the role of newspapers and journals in constructing the public images of the mammoth in Catalonia in the late 19th and early 20th centuries, paying special attention to the visual power of descriptions, pictures and cartoons of this and other ancient species that increasingly appeared in the press. As palaeontology became a 'public science, ' the extinct species gained status not least because it could be imbued with multiple meanings that moved between the scientific and public spheres. The visualizations of the animal contributed to metaphorically reinforcing and confronting ideas of political and social scope, like the notions of modernity and national identity, which were of great relevance in Barcelona at the turn of the century.